Răspuns :
2(x - 3) + 7(2x - 1) = 19 - 4(x +2)
2x - 6 + 14x - 7 = 19 - 4x - 8
16x - 13 = 11 - 4x
16x + 4x = 11 + 13
20x = 24
x = 24/20
x = 6/5
2x - 6 + 14x - 7 = 19 - 4x - 8
16x - 13 = 11 - 4x
16x + 4x = 11 + 13
20x = 24
x = 24/20
x = 6/5
[tex] \it 2 \cdot (x - 3) + 7(2x - 1) = 19 - 4(x + 2) = = > \\ \it 2x - 6 + 14x - 7 = 19 - 4x - 8 = = > \\ \it 2x + 14x - 6 - 7 = 19 - 4x - 8 = = > \\ \it 16x - 13 = 19 - 4x - 8 = = > \\ \it 16x + 4x = 13 + 19 - 8 = = > \\ \it 20x = 32 - 8 = = > \\ \it 20x = 24 = = > \\ \it x = \frac{24}{20}^{(4} = = > x = \it \frac{6}{5} \\ \\ [/tex]